Membaca Tingkat Kesejahteraan Perajin Batik Kemitraan UMKM Di Tanjung Bumi Melalui Maqāṣid Al-Sharīʻah - Nasik, Khoirun (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
Referring to data from the Bangkalan Department of Industry and Trade in 2020, currently the number of batik artisans in Bangkalan Regency reaches 1,500,000 spread across Tanjung Bumi, Kokop, Modung and Burneh sub-districts. The majority of the wages earned for each piece of good quality batik is Rp. 300-500 thousand which takes 1-3 months and Rp. 75,000 per piece for ordinary batik cloth which can be completed in 1-2 weeks. In Tanjung Bumi District, in 2019 there was a group of batik artisans who partnered with the Bajumi MSMEs that succeeded in increasing their income. The purpose of this study is to analyze the welfare level of batik artisans in partnership with SMEs who apply a profit sharing system (nisbah) with maqoshid sharia indicators that combine outward and inner aspects. This research strengthens the partnership model of craftsmen and MSMEs as an effort to accelerate the improvement of welfare as well as poverty alleviation as well as the third cluster poverty alleviation program, namely MSME-based. This research is descriptive with a qualitative approach. While the techniques used are interviews, observation and documentation. The analysis used in this research is deduction. The results showed that the welfare of the batik artisans of the Bajumi UMKM partnership had an impact on the welfare at the dloruriyat level in the aspect of hifdlun nasl, while hifdlu din, hifdlun nafs, hifdlu aql were at the hajiyat level and hifdlul mal were at the tahsiniyat level